Cellular mechanism for the improvement of multiple stress tolerance in brewer's yeast by potassium ion supplementation. (8th January 2020) - Xu, Yingchao; Yang, Huirong; Brennan, Charles S.; Coldea, Teodora Emilia; Zhao, Haifeng
Summary: The ethanol fermentation efficiency was affected by multiple stress tolerance of yeast during brewing and bioethanol industry. The effect of KCl on the multiple stress tolerance of yeast cells was examined. Results showed that KCl addition significantly enhanced the tolerance of yeast cells to osmotic and ethanol stress, which correlated with the decreased membrane permeability, the increased intracellular ergosterol and ATP content, and the improved activity of complex II and complex III in yeast cells. Biomass and viability of yeast cells under osmotic and ethanol stress were increased significantly by KCl addition. Supplementation of 4 and 10 g L −1 KCl exhibited the best promotion activity for yeast cells present in medium with 500 g L −1 sucrose and 10% (v v −1 ) ethanol, respectively. These results suggested that exogenous potassium addition might be an effective strategy to improve yeast tolerance and fermentation efficiency during industrial very‐high‐gravity (VHG) fermentation. Abstract : Potassium ion supplementation improves the multiple stress tolerance in brewer's yeast.